DH pedagogy @LINHD : DH Training in Spanish: Digital Humanities as an e-learning platform to teach between Spain and Latin America - González-Blanco, Elena (2016)
The creation of the first Digital Humanities Innovation Lab (LINHD), hosted by the Spanish National Distance University (UNED) in 2014, opened a new a new opportunity for courses and and certificates in Digital Humanities for the Spanish speaking world. While the digital switch and interdisciplinarity in the Humanities has hardly been applied to the majority of public Spanish Universities, LINHD has proudly invested time and energy in the creation of an innovative training way oriented to digital humanities and offered mostly as an online education. Our presentation will offer a general overview of the three main initiatives: standalone courses and seminars, two long specialized degrees on DH basics and digital editions, and a yearly summer school. All these initiatives have boosted the birth of this discipline in the Spanish-speaking world, generating new DH materials (in Spanish and adapted to diverse profiles of Humanities Spanish Speaking students), new types of students? assessments, and innovations and challenges for Digital Humanities as a discipline for which online training has proven to be a successful way of approaching people from different countries and places. LINHD launched its first DH summer school: "Introducción a las Humanidades Digitales" in July 2014, getting more than 50 students involved. The summer school was followed by a longer DH program of 30 units, lasting from December to September and amplifying all the contents that had been announced in the summer school. The strategy has been similar in the following years, in 2015, summer school was devoted to digital scholarly editing and a new longer winter training program was launched for 2015-2016. This last year, we decided to focus on DH methodologies applied to a specific field, poetry, which had as a result a high-quality summer school on this topic that is at the heart of LINHD projects and research interests. Taking into account the interests of the community, the needs of the field and the offers of new programs in different places, our new proposal for this year, starting in January 2017 is stylometry, a technique that is still very much unknown for Spanish DH research.Our strategy for designing curricula for all these programs has been twofold: first, we have always had as a model the reference curricula for DH above mentioned, together with the needs of the scholars in our own environment. The keys for success have been three: having a DH compliant interdisciplinary teaching faculty, variety in contents (our first DH course covered a huge range of topics going from databases, TEI markup, semantic web, visualization to digital libraries), and flexibility to change thanks to the lessons learned every year.